136k views
5 votes
An = 12 + (n − 1).–2HELPPPP

User Bgomberg
by
4.9k points

1 Answer

5 votes

Solution

Step 1

Substitute for n = 101 in the equation


\begin{gathered} a_n=12\text{ + (n-1).-2} \\ a_n=12\text{ +(101-1).-2} \end{gathered}

Step 2

Simplify the problem


\begin{gathered} a_n=12\text{ +100.-2} \\ a_n=12\text{ + }(-200) \\ a_n=12-200 \\ a_n=-188 \end{gathered}

User Sasidharan
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.